2011
DOI: 10.1007/s10750-011-0835-9
|View full text |Cite
|
Sign up to set email alerts
|

Trade-off between vegetative regeneration and sexual reproduction of Sargassum thunbergii

Abstract: An ecological demographic study was conducted from January to December 2009 at Changshan Island on the northern side of Shandong Peninsula, China. The study investigated stem regeneration and the resource trade-off between sexual reproduction and vegetative regeneration of the brown alga Sargassum thunbergii at the individual thallus level. Stem regeneration from the holdfast occurred year round but with significant seasonality, peaking in the early summer. Both percentage of fertile stems and reproductive eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…thunbergii , consistent with prior studies (Umezaki, 1974;Koh et al, 1993;Zheng and Chen, 1993). The transition between the short and long length size classes suggests that there is a trade-off between sexual reproduction and vegetative regeneration, as noted by other authors (McCourt, 1984;Chu et al, 2011).…”
Section: Discussionsupporting
confidence: 61%
“…thunbergii , consistent with prior studies (Umezaki, 1974;Koh et al, 1993;Zheng and Chen, 1993). The transition between the short and long length size classes suggests that there is a trade-off between sexual reproduction and vegetative regeneration, as noted by other authors (McCourt, 1984;Chu et al, 2011).…”
Section: Discussionsupporting
confidence: 61%
“…Åberg (1996) demonstrated differences in the annual reproductive effort of Ascophyllum nodosum between small and large individuals, which were interpreted as a reproductive trade-off by arguing that small individuals are better off investing in growth, which offers them a better chance of survival, while larger individuals can afford to invest in reproduction. By removing either vegetative stems or reproductive structures in Sargassum thunbergii, Chu et al (2011) demonstrated a trade-off between vegetative growth and reproduction. This study confirmed older observations by McCourt (1985) and Gillespie and Critchley (2001) of an inverse correlation between vegetative growth and reproductive effort among different Sargassum species in the Gulf of California and South Africa, respectively.…”
Section: Age and Sizementioning
confidence: 99%
“…receptacles and sporophylles) (Vernet and Harper 1980;McCourt 1985;Ang 1992;Mathieson and Guo 1992;Åberg 1996;Zou et al 2011). While a reproductive cost, like growth reduction or decrease of survival rate, has been observed in various fucoids (McCourt 1985;Ang 1992;Mathieson and Guo 1992;Åberg 1996;Chu et al 2011), the existence of resource trade-off in algae has been discussed, because reproductive organs are normally pigmented and potentially able to photosynthesis before the release of spores or gametes (De Wreede and Klinger 1990). However, the reproductive period coincide generally with the end of growth and can be followed by the senescence and the death of the parental thallus (Zou et al 2006).…”
Section: Introductionmentioning
confidence: 99%